2016
DOI: 10.1016/j.ijid.2016.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and effectiveness of facemask against respiratory infections at mass gatherings: a systematic review

Abstract: A modest proportion of attendees of MGs use facemask, the practice is more widespread among health care workers. Facemask use seems to be beneficial against certain respiratory infections at MGs but its effectiveness against specific infection remains unproven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
77
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 61 publications
2
77
0
5
Order By: Relevance
“…The high rate of facemask use (almost 80%) observed among French Hajj pilgrims during the 2009 influenza pandemic year [50], compared to about 55% in a non-pandemic year [3], and in pilgrims from Southeast Asia (e.g., 73% among Malaysian pilgrims in 2007) seem to be due to cultural differences and heightened awareness during a pandemic [51]. The lower uptake of facemasks among participants in our cRCT is similar to the uptake among Saudi Arabian (35 to 57%) and Australian pilgrims (53 to 57%) observed in previous surveys [31,32,52,53], while uptake as low as 0.02% was also recorded among some international pilgrims [54]. Although 78% in the intervention group of our cRCT used facemasks, only a quarter used them regularly.…”
Section: Plos Onesupporting
confidence: 80%
“…The high rate of facemask use (almost 80%) observed among French Hajj pilgrims during the 2009 influenza pandemic year [50], compared to about 55% in a non-pandemic year [3], and in pilgrims from Southeast Asia (e.g., 73% among Malaysian pilgrims in 2007) seem to be due to cultural differences and heightened awareness during a pandemic [51]. The lower uptake of facemasks among participants in our cRCT is similar to the uptake among Saudi Arabian (35 to 57%) and Australian pilgrims (53 to 57%) observed in previous surveys [31,32,52,53], while uptake as low as 0.02% was also recorded among some international pilgrims [54]. Although 78% in the intervention group of our cRCT used facemasks, only a quarter used them regularly.…”
Section: Plos Onesupporting
confidence: 80%
“…Previous studies have not explored if demographic factors were associated with an intention to use non-pharmacological protective measures before travel and their actual use during Hajj. Nonetheless, earlier studies did conclude that health education prior to departure was significantly associated with greater compliance with preventative practices, particularly the use of facemasks and hand sanitizers [19][20][21][22].…”
Section: Discussionmentioning
confidence: 96%
“…It has also been argued that it can help in reducing the number of times a person touches the face/mouth/nose with unwashed hands, which can significantly reduce the chance of infection. Previous studies have also demonstrated the effectiveness of face masks in protecting against respiratory infection during Hajj (Elachola et al, 2014;Barasheed et al, 2016).…”
Section: G R a P H I C A L Abstractmentioning
confidence: 95%